APLIKASI PENCARIAN LOKASI PANTI ASUHAN DI KOTA AMBON BERBASIS MOBILE - Irawati, Irawati; Aswin, Hafiza; Salim, Yulita (Program Studi Teknik Informatika Fakultas Ilmu Komputer Univeristas Muslim Indonesia, 2018)
The diverse population of Ambon City has led to a diversity of spiritual beliefs that can be found in this city, this also has an impact on the orphanages built in Ambon City. Based on the source www.malukuprov.go.id, which is the official address of the Ambon City Government website, there is no information relating to the orphanage. As a result, donors in Ambon City experienced difficulties in getting accurate information about orphanages, because limited information from prospective donors took the initiative by asking the public to obtain information about the local orphanage. The location search application for this orphanage was built using the Location Based Service (LBS) system that can provide information on routes to orphanages to donors through mobile android users equipped with navigation features and display information about the related orphanage to facilitate donors in concluding the orphanage which ones need more donations.